BUSANA KEPANDITAAN HINDU BALI - Ida Bagus Purwa Sidemen -; I Ketut Winantra -; I Kadek Satria -; Ida Bagus Ngurah Bradijaya Manuaba - (UNHI PRESS, 2023)
ABSTRACT A Pandita or more widely known as Sulinggih in Bali, apart from being regulated by the provisions of the kasulinggihan gym (behavior), is also regulated by how to dress. Pandita or Sulinggih clothing is regulated in several literary sources such as Siwa Sasana and Silakrama, including several provisions that are made and regulate the conditions for Sulinggih clothing according to the aguron-guron or penbean system. There are two types of dressing procedures as a Pandita or Sulinggih, namely clothing worn daily or not in order to carry out the duties of ngelokapalasraya and clothing when ngelokapalasraya leads a yadnya. Some important clothing for a Pandita or Sulinggih when leading a yadnya ceremony include; wastra, kampuh, kawaka, pepetet, sinjang, santog, slimpet/sampet/paragi, kakasang, rudrakacatan aksamala, kanta bharana, karna bharana/kundala/gondala, astha bharana/guduita/gudhuha, angustha bharana, bhawa/ketu/amakuta/swetambhawa , and sign. Keywords: Clothing, Pandita, Balinese Hinduism